Trace metal contents in the mussel Mytilus galloprovincialis from Atlantic coastal areas in northwestern Morocco: Levels of contamination and assessment of potential risks to human health. (June 2022) - Kouali, Hassnae; Chaouti, Abdellatif; Achtak, Hafid; Elkalay, Khalid; Dahbi, Abdallah
Abstract: The bioaccumulation of trace metals Cd, Cr, Cu and Zn in soft tissues of the mussel Mytilus galloprovincialis was studied seasonally along the Atlantic coast of northwestern Morocco. Average concentrations (μg g −1 dry weight) decreased in the following order: Zn (141.61 ± 78.06) > Cr (22.57 ± 15.47) > Cu (18.95 ± 20.01) > Cd (16.33 ± 19.01), with higher amounts during wet seasons. The " Metal Pollution Index " and " Individual Multimetal Bioaccumulation Index " suggested a higher mussel contamination in industrialized areas. Moreover, Cd and Cr concentrations were above the permissible guidelines' limits. The related risks to human health associated with mussel consumption were also assessed. The " Target Hazard Quotient " for Cd and Cr revealed a threat to children when mussels originated from polluted stations, while the " Hazard Index " indicated a hazard to them in all stations. Regarding the " Maximum Safe Consumption ", children should not consume mussels, even in low quantities. This study represents the first datum in Morocco to assess such a risk to human health. Graphical abstract: Unlabelled Image Highlights: Human health risk assessment of trace metals in mussels was investigated in Morocco. This result contributes to a database regarding the safety of mussel consumption. Cd and Cr have potential health risks, especially for children. The overall risk from exposure to multiple metals in mussel should be of concern. Consumption rate of mussels should be limited to minimize the metal health risks.